2020
DOI: 10.5114/pg.2020.93629
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Clostridium difficile infection in adults

Abstract: Clostridium difficile infection (CDI) has become a serious medical and epidemiological problem, especially in well developed countries. There has been evident increase in incidence and severity of CDI. Prevention, proper diagnosis and effective treatment are necessary to reduce the risk for the patients, deplete the spreading of infection and diminish the probability of recurrent infection. Antibiotics are the fundamental treatment of CDI. In patients who had recurrent CDI fecal microbiota transplantation seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 65 publications
0
25
0
29
Order By: Relevance
“…The use of PTZ was profoundly associated with OS. PTZ has a significant effect on the gut microbiota, and some studies indicate a substantial decrease in anaerobic commensals four to eight days after using it [ 26 , 27 , 28 ]. Specifically, PTZ reduces the population profile of Bifidobacterium , Eubacterium and Lactobacillus in human gut microbiota [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of PTZ was profoundly associated with OS. PTZ has a significant effect on the gut microbiota, and some studies indicate a substantial decrease in anaerobic commensals four to eight days after using it [ 26 , 27 , 28 ]. Specifically, PTZ reduces the population profile of Bifidobacterium , Eubacterium and Lactobacillus in human gut microbiota [ 26 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of COVID-19 is mainly symptomatic and is based on international research and guidelines [7,8]. Drugs recommended include chloroquine, hydroxychloroquine, azithromycin and lopinavir/ritonavir [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Castagliuolo et al reported that the 54-kDa protease of Saccharomyces bourardii degrades both CD toxin and its brush border membrane receptor, thus protecting rats from CD enteritis [ 42 ]. However, the clinical effect of probiotics on CDAD is controversial [ 43 , 44 ]. Further efforts to explore the detailed mechanisms by which human gut microbes antagonize CD are necessary to establish strategies to control refractory CDAD.…”
Section: Discussionmentioning
confidence: 99%